Switchable Two‐Terminal Transparent Optoelectronic Devices Based on 2D Perovskite - Kumar, Mohit; Patel, Malkeshkumar; Park, Dae Young; Kim, Hong‐Sik; Jeong, Mun Seok; Kim, Joondong (Advanced electronic materials, 2019)
A switch‐like structure that can be turned on/off with photons is considered necessary for most optoelectronic devices, such as phototransistors and photodetectors. However, developing a single device whose photoresponse can be modulated without changing the measuring voltage or illuminating light is challenging, and yet to be achieved. In this work, a conceptually new 2D perovskite‐based fully transparent two‐terminal optoelectronic device that can be turned on/off with a short electric pulse without any further change in the measuring conditions, such as the illuminating photon or applied voltage is proposed and demonstrated. The device exhibits loop opening in the current–voltage characteristics, which is utilized to design the novel electrically triggered optoelectronic device. The photocurrent of the device can be modulated from zero to 2.2 mA using a simple voltage pulse. Further, a responsivity of 550 mA W−1 and detectivity of 2.16 × 1010 Jones are measured in the on‐state. Potentially, the approach opens a new avenue for the design of two‐terminal advanced highly transparent optoelectronic devices, such as smart windows and transparent image sensors. A conceptually new 2D perovskite‐based fully transparent two‐terminal optoelectronic device is proposed and demonstrated, which can be turned on/off with a short electric pulse without any additional change in the measuring conditions. The photocurrent of the device can modulate from zero to 2.2 mA. Further, a responsivity of 550 mA W−1 and detectivity of 2.16 × 1010 Jones are measured in the on‐state.